Inhibition of avian influenza A virus H5N1 by using methylene blue with laser treatment in vitro - Nguyen, Hung Chi; Tong, Quang Cong; Tran, Quoc Tien; Nguyen, Trung Nam (Vietnam Journal of Biotechnology, 2025)
The avian influenza virus H5N1 causes the death of millions of avians, including the risk of viral infection in humans. In photodynamic therapy, photosensitizers with light and molecular oxygen might result in the death of cells by generating cytotoxic molecules. Photosensitizers such as methylene blue and laser treatment have been demonstrated to have high efficacy against several types of viruses. The anti-H5N1 effects of several photosensitized compounds, such as methylene blue with laser treatment, are not known. We found that the titer of the ST-2009 virus was 10 × 107 pfu/mL via the MDCK plaque assay. Methylene blue treatment at 0.1 to 1.0 µM had safe effects on MDCK cells. In this study, we demonstrated that the titers of the ST-2009 virus were 3.9 log10 pfu/mL, 5.7 log10 pfu/mL and 6.8 log10 pfu/mL without the methylene blue treatment, but no ST-2009 virus titer was detected after treatment with 0.5 μM methylene blue. In addition, the survival of the ST-2009-infected MDCK cells was significantly greater when the cells were treated with 0.5 to 1.0 μM methylene blue in combination with a laser for 80 s at 16 J/cm2 than in the nontreated control. The survival rates of the MDCK cells were 98.1 ± 0.2 and 96.7 ± 0.4% when the laser treatment (80 s and 16 J/cm2) was combined with 0.5 and 1.0 μM methylene blue, respectively. In addition, without laser treatment or the addition of 0.5 or 1.0 μM methylene blue, the percentages of living cells significantly decreased to 8.3 ± 0.3 and 6.3 ± 0.2%, respectively. The survival of MDCK cells without the addition of methylene blue was 7.5 ± 0.4%, whereas that without laser treatment was 4.6 ± 0.5%. In summary, photosensitizers such as methylene blue with laser treatment can be suitable therapies for the inhibition of avian influenza A virus H5N1.